# 10th cbse maths solution for exercise 3.6 part 2

This page 10th cbse maths solution for exercise 3.6 part 2 is going to provide you solution for every problems that you find in the exercise no 3.6

## 10th CBSE maths solution for Exercise 3.6 part 2

(iv) 5/(x – 1) + 1/(y – 2) = 2

6/(x – 1) – 3/(y – 2) = 1

Solution:

Let 1/(x – 1) = a and 1/(y – 2) = b

5 a + b = 2  --------(1)

6 a – 3 b = 1  --------(2)

(1) x 3 => 15 a + 3 b = 6

6 a – 3 b = 1

-----------------

21 a = 7

a = 7/21

a = 1/3

1/(x-1) = 1/3

3 = x -1

x – 1 = 3

x = 3 + 1

x = 4

Substitute a = 1/3 in the first equation

5(1/3) + b = 2

(5/3 )+ b = 2

b =  2 – (5/3)

b = 1/3

1/(y – 2) = 1/3

3 = y – 2

y – 2 = 3

y = 3 + 2

y = 5

(v)  (7 x - 2 y)/xy = 5

(8 x + 7 y)/xy = 15

Solution:

(1) x 7 = > - 14 a + 49 b = 35

(2) x 2 = >  14 a + 16 b = 30

-----------------------

65 b = 65

b = 1

Substitute b = 1 in the first equation

-2 a + 7 (1) = 5

-2a + 7 = 5

- 2a = 5 -7

-2a = -2

a = 1

1/x = a             1/ y = b

1/x = 1             1/y = 1

x = 1       y = 1

(vi) 6 x + 3 y = 6 xy

2 x + 4 y = 5 xy

Solution:

Dividing the whole equation by xy

(6 x/xy) + (3y/xy) = (6xy/xy)

(2x/xy) + (4y/xy) = (5xy/xy)

(6/y) + (3/x) = 6

(2/y) + (4/x) = 5

1/x = a and 1/y = b

3 a + 6 b = 6  ---------(1)

4 a + 2 b = 5  ---------(2)

3 a + 6 b = 6

(2) x 3 =>12 a + 6 b =  15

(-)      (-)       (-)

---------------------

-9a  = - 9

a = 1

Substitute a = 1 in the first equation

3(1) + 6 b = 6

3 + 6 b = 6

6 b = 6 – 3

6 b = 3

b = 3/6

b = 1/2

1/x = a            1/y = b

1/x = 1             1/y = 1/2

x = 1                   y = 2

Related pages 